Hematological Profiles of Green Sea Turtle (Chelonia mydas) Rehabilitated at Turtle Conservation and Education Center, Serangan Island, Denpasar, Bali - Agustina, Leoni Arifah; Dharmawan, Nyoman Sadra; Adnyana, Ida Bagus Windia (Jurnal Veteriner, 2020)
Threat of extinction results in the increasing sea turtle conservation efforts through scientific research in recent years. During rehabilitation process, the non-invasive blood analysis is considered to be highly valuable to determine sea turtle’s health. The objective of this study was to assess the hematological profiles of green sea turtles (Chelonia mydas) under rehabilitation at Turtle Conservation and Education Center (TCEC) Serangan Island, Denpasar, Bali. Three mililiters of peripheral blood from healthy green sea turtles were collected from cervical dorsal sinuses and kept in heparinized vacutainer tube before proceeded with hematological evaluation. PCV was determined by microhematocrit method. Diff count and thrombocyte percentage were determined using Giemsa-stained blood smear under the microscope. RBC and WBC total count were determined using hemocytometer. Hemoglobin (Hb) value was determined using Sahli method. Each hematological values were then analyzed using descriptive analysis. The correlation between body condition index (BCI) and hematological values were analyzed using Spearman’s rank correlation test. The mean values evaluated was 7.28 g/dL in Hb, 31.35% in PCV, 0.67 x 106/?L in total RBC count, 479.37 fl in MCV, 111.38 pg in MCH, 23.42 g/dL in MCHC, 4.01 x 103/?L in total WBC count, 1.20 x 103/?L in lymphocyte, 0.21 x 103/?L in monocyte, 0.10 x 103/?L in eosinophil, 2.48 x 103/?L in heterophil and 0.01 x 103/?L in basophil. No significant correlation was found between the BCI and hematological profiles evaluated.